The revolution starts at home: Confronting intimate violence within activist communities - Chen, Ching-In; Dulani, Jai; Piepzna-Samarasinha, Leah Lakshmi (AK Press, 2016)
The Revolution Starts at Home is as urgently needed today as when it was first published. This watershed collection breaks the dangerous silence surrounding the “secret” of intimate violence within social justice circles. Just as importantly, it provides practical strategies for dealing with abuse and creating safety without relying on the coercive power of the state. It offers life-saving alternatives for survivors, while building a movement where no one is left behind.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; justice sociale; militance; thématiques; violences; violences conjugales; violences contre les femmes*; violences d'état

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Postures et privilèges - Institut de recherches et d'études féministes (FéminÉtudes, 2016)
Ce nouveau format de publication tend vers le livre d’artistes et illustres autant les postures féministes que ces privilèges. Postures & Privilèges, voilà un thème qui s’impose. Parce que les oppressions sont multiples; parce que les féminismes sont pluriels. Parce que les luttes tirent précisément leur force et leur vitalité de cette diversité d’expériences, de points de vue et de positionnements théoriques dans lesquels chaque féministe se construit. Et parce qu’en étant plurielles, on peut être allié.e.s et solidaires, veut-on espérer. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-21-no-1-2016-postures-et-privileges/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; création; cyberféminisme; féminétudes; identités LGBTQIA2+; justice sociale; maternité; militance; personnes trans*; privilèges; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; écriture des femmes*

La portée réparatrice et réconciliatrice de la Commission de vérité et réconciliation du Canada - Jaccoud, Mylène (Recherches amérindiennes au Québec, 2016)
Cet article examine les potentialités réparatrices et réconciliatrices de la Commission de vérité et réconciliation (CVR) qui a été mise en place au Canada de 2008 à 2015 en réponse aux traumatismes vécus par les autochtones dans les pensionnats. L’auteure conclut que ces potentialités sont relativement limitées. Les principales limites tiennent à l’absence d’un espace de dialogue entre les victimes et les responsables, à une centration sur les narratifs traumatiques des victimes mais aussi à une conception dépolitisée du principe de la réconciliation. La CVR du Canada n’a pas inscrit la décolonisation comme vecteur de réconciliation mais a préféré s’engager dans la voie d’une pacification des relations entre les peuples. Or, l’auteure soutient que la réconciliation entre les peuples autochtones et l’État nécessite de dépasser les gestes de guérison et de réparation matérielle ou symbolique. La décolonisation des institutions, la redistribution des territoires et une réforme constitutionnelle en profondeur restent les seules avenues possibles pour parvenir à réconcilier avec ses oppresseurs un peuple victime d’un génocide culturel.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; capitalisme; commission de vérité et réconciliation; cours; criminologie; discipline; droits des personnes autochtones; féminisme décolonial; histoire et politique; justice réparatrice; justice sociale; peuples autochtones; pol4102; premier cycle; périodes historiques; racisme; réconciliation; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences